IC 6604 Methods And Costs Of Concentrating Scheelite Ore At The Silver Dike Mill, Mineral County, Nev. - Introduction - William O. Vanderburg (The National Institute for Occupational Safety and Health (NIOSH), 1932)
This paper describing the methods and costs of milling scheelite ore at the Silver Dike concentrator of the Nevada-Massachusetts Co., Inc., is one of a series being prepared by the Bureau of Mines. In the Silver Dike mill tungsten ore which contains about 1 per cent of scheelite is treated at the maximum rate of 45 tens per 24 hours by tabling followed by magnetic separators to clean the table concentrates. Unusually high-grade concentrates are produced which average between 70 and 75 per cent of W03.